Autonomic Neuropathy - Dineen, Jennifer; Freeman, Roy (Seminars in Neurology, 2015)
Autonomic nerve fibers are affected in most generalized peripheral neuropathies. Although this involvement is often mild or subclinical, there are a group of peripheral neuropathies in which the small or unmyelinated fibers are selectively or prominently targeted. These include the autonomic neuropathies associated with diabetes and amyloid, immune-mediated autonomic neuropathies including those associated with a paraneoplastic syndrome, inherited autonomic neuropathies, autonomic neuropathies associated with infectious diseases, and toxic autonomic neuropathies. The presenting features include impairment of cardiovascular, gastrointestinal, urogenital, thermoregulatory, sudomotor, and pupillomotor function. The accurate diagnosis of the autonomic neuropathies has been enhanced by the availability of physiological tests that measure autonomic function, and more recently, structural studies of the autonomic cutaneous innervation. With the help of these investigations and the judicious use of laboratory testing, many autonomic neuropathies can be accurately diagnosed and their clinical progression monitored.
Keywords: autonomic neuropathy; diabetic neuropathy; amyloid neuropathy; immune-mediated neuropathy; toxic neuropathy; orthostatic hypotension; cardiac autonomic neuropathy